Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
p = 125/73
Step-by-step explanation:
−p − 13 = −43p + 23 (5p − 6)
−p − 13 = −43p + 115p − 138
−p − 13 = 72p − 138
+p +p
-----------------------------
-13 = 73p - 138
+138 +138
-----------------------------
125 = 73p
/73 /73
-----------------------------
125/73 = p
If you need the answer in mixed fraction, then it's --> p = 1 52/73
The solution to the given equation is p = - 1.71
To determine the solution of the given equation,
We will find the value of the variable, p, that satisfies the equation.
From the question, the given equation is
[tex]-p-13 = -43p+23(5p-6)[/tex]
To solve this,
First, Clear the brackets
[tex]-p-13 = -43p + 115p - 138[/tex]
Now, Collect like terms
[tex]-p +43p -115p = -138 + 13[/tex]
[tex]73p = -125[/tex]
Now, divide both sides of the equation by 73
[tex]\frac{73p}{73} = \frac{-125}{73}[/tex]
∴ p = - 1.71
Hence, the solution to the given equation is p = - 1.71
Learn more here: https://brainly.com/question/9956738
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.